Dynamic Model Test Based on Shaking Table of Wudongde High Arch Dam - XIONG Kun; HU Qingyi; CAO Quxiu (Renmin Zhujiang)
At present,there are few examples of high arch dams subjected to earthquakes in China and abroad,and there is a lack of sufficient and effective observation data of prototype seismic damage.Based on the shaking table dynamic model test,the seismic behaviors and damage process are studied for the 270 m-high Wudongde arch dam.The dam’s seismic failure mode of the dam body and structural seismically weak parts under strong earthquakes are compared and its seismic safety is evaluated.The results show that the model test analysis can obtain natural vibration characteristics and dynamic responses such as acceleration,dynamic strain,and transverse joint aperture under earthquakes,which are consistent with the numerical calculation results.Under extremely strong earthquakes,there are local cracks with limited extension depth near the foundation surface of the dam.The main damage area lies in the middle and upper part of the dam body,and horizontal macroscopic cracks occur in the area within about 1/3 of the height below the dam crest connecting the upstream and downstream.It is proved that the Wudongde high arch dam has a better stress condition,a smaller transverse joint aperture,and a higher ultimate seismic capacity under the design and calibrated earthquakes.